The Effect of the Enteral Correction Program on Oxidative Stress Parameters in Patients with Poisoning with Psychopharmacological Agents or Corrosive Substances - M. B. Belova; E. V. Klychnikova; M. M. Potskhverya; A. S. Bogdanova; A. Yu. Simonova; E. V. Tazina (Неотложная медицинская помощь)
RATIONALE Acute exogenous poisonings represent a serious medical problem due to the prevalence, severity of the course and high lethality. In their pathogenesis, an important place is given to oxidative stress (OS). Among modern methods of treatment of acute poisoning, the attention is drawn to approaches aimed at normalizing homeostatic indicators by cleansing the enteric environment, restoration of its barrier function.PURPOSE OF THE STUDY Assess the impact of the enteral correction program (ECP) on the parameters of lipid peroxidation (LPO) and antioxidant systems in acute exogenous poisoning.MATERIAL AND METHODS 119 patients who underwent treatment at the N.V. Sklifosovsky Research Institute for Emergency Medicine, of which 45 were with severe acute poisoning with psychopharmacological agents (PPPA) and 74 with poisoning with corrosive substances (PCS). The two study groups consisted of 40 patients with PCS and 23 patients with PPPA, whose standard therapy was supplemented with ECP. The ECP included making intestinal lavage on admission, the introduction of glucosed saline enteral solution in the following days; and for patients with PCS the treatment also included enteral nutrition and Pektovit.The comparison groups included 56 people (34 with PCS and 22 with PPPA) comparable to the patients of the study groups by sex, age, the type and severity of poisoning poisoning treated with standard therapy The severity of OS was assessed by the KMDA/TAA index which was calculated by means of measuring the concentration of malonic dialdehyde (as an LPO parameter) and total antioxidant activity in the blood plasma of the patients. Serum levels of nitric oxide stable metabolites were also measured.The analysis of the results was performed with the regard to patient’s age.RESULTS In patients of working age, regardless of the toxicant type, LPO activation occurred, which was expressed with an increased KMDA/TAA by 1.4–1.8 times compared to the norm. Using ECP at the study stages contributed to maintaining this balance level between pro- and antioxidants. In patients of comparison groups there was an increase in the LPO system imbalance, while KMDA/TAA exceeded the norm by 2.2–2.4 times that was statistically signiﬁ cantly different from the parameters in the study groups.Older patients showed decreased levels of LPO products, the total antioxidant activity compared to the normal for the age, and, as a result, a decrease in KMDA/TAA by 1.3–1.5 times in PCS and by 2–2.4 times in PPPA. This is due to the low adaptive potential of this category of patients. In this age group, ECP contributed to a moderate activation of LPO, which provided the trend towards normalization of OS parameters.CONCLUSIONS The use of the enterable correction program has a positive impact on the dynamics of oxidative stress parameters, ensuring the maintenance of oxidative processes at the level required for an adequate protective reaction of the body to chemical injury.